Epilepsy in children with tuberous sclerosis complex: Chance of remission and response to antiepileptic drugs. (4th June 2015) - Overwater, Iris E.; Bindels‐de Heus, Karen; Rietman, André B.; ten Hoopen, Leontine W.; Vergouwe, Yvonne; Moll, Henriette A.; de Wit, Marie‐Claire Y.
Summary Objective To describe treatment and outcome of epilepsy in children with tuberous sclerosis complex (TSC). Methods Seventy‐one children with TSC and epilepsy treated at the ENCORE TSC Expertise Center between 1988 and 2014 were included. Patient characteristics and duration and effectiveness of antiepileptic treatments were extracted from our clinical database. Correlations were made between recurrence of seizures after response to treatment, and several patient characteristics. Results Median age at time of inclusion was 9.4 years (range 0.9–18.0). Seizure history showed that 55 children (77%) of 71 became seizure‐free for longer than 1 month, and 21 (30%) of 71 for longer than 24 months. Remission of seizures was associated with higher IQ, and a trend was observed between seizure remission and age at onset of seizures. A total of 19 antiepileptic drugs (AEDs) were used. Valproic acid, vigabatrin, levetiracetam, and carbamazepine were used most frequently. Nonpharmacologic therapies (ketogenic diet, epilepsy surgery, and vagus nerve stimulation) were used 13 times. Epilepsy surgery was most effective, with four of five children becoming seizure‐free. AEDs prescribed as first and second treatment were most effective. Valproic acid was prescribed most frequently as first and second treatment, followed by vigabatrin. Thirty‐one children had infantile spasms, preceded by focal seizures in 18 children (58%). Vigabatrin was used by 29 children (94%), and was first treatment in 15 (48%). Vigabatrin was more effective than other AEDs when prescribed as first treatment. Significance We showed that, although 77% of children with epilepsy due to TSC reached seizure remission, usually after their first or second AED, this was sustained for at least 24 months in only 38%. Almost half of those with 24 months of remission later had relapse of seizures. Our results support vigabatrin as first choice drug, and show the need for better treatment options for these children.